Peran Pemimpin Organisasi Intra Kampus dalam Membangun Komunikasi - Shodiq, Abdulloh (Moderasi : Journal of Islamic Studies, 2023)
Communication of the Nahdlatul Ulama Pasuruan University Student Executive Board is a discourse that places communication and interaction activities in the corridors of the intra-campus student organization which is an executive institution at the Islamic higher education level of NU Pasuruan which is led by a student president. This research uses qualitative research methods, data is collected through indirect observation and interviews from primary and secondary data sources. In this organization, leaders have an important role, therefore a leader should have the following leadership characteristics: (1) clever and intelligent (fathonah), (2) honest and truthful (siddiq), (2) brave to take risks and take responsibility (amanah), and (4) transformative and oriented towards the future of Islamic society (tabligh).